Phenotypic characterization of three Venezuelan sweet pepper (Capsicum chinense Jacq.) - Laurentin, Hernán (2020)
Introduction. The cultivated species of the genus Capsicum, among them C. chinense, are known for the pungency of their fruits, however, there are several types of this pepper that do not present pungency. Venezuelan cuisine is defined by the characteristic flavor of a class of peppers that do not present pugency, which are called sweet peppers. Among these, the best known and most used are the cultivars Rosita, Pepon, and Llanero. Objective. To characterize the Rosita, Pepon, and Llanero chilli pepper cultivar by means of 53 morphological characteristics and to determine the phenetic relationship among them. Material and methods. In a randomized block design with three treatments (cultivars) and five repetitions, 45 seedlings of each cultivar were arranged in La Vigia, Jimenez municipality of Lara state, Venezuela, in August 2017. The transplant was carried out in separate rows at 0.50 m, and the seedlings were spaced 0.50 m apart on the row. On the three plants of the central row of each experimental unit (fifteen plants in total for each cultivar) the category or value of attributes of stem, leaf, flower, fruit, and seed were determined. Results. Forty-two percent of these attributes were variable among the plants evaluated, fifteen of them were categorical and seven quantitative, and significant differences (p<0.05) were detected among cultivars. Flower and seed characteristics showed no variation among cultivars, while stem and fruits showed the greatest variation. As a whole, the morphological characteristics that presented variation allowed to identify each one of the cultivars and therefore, to discriminate them. Conclusion. The variation identified in the characteristics of the fruit is indicative of the potential for genetic improvement of the Venezuelan sweet pepper in its commercial part.